State Bar of California Annual Meeting at San Diego Town and Country Hotel - Watkins, Howard::::::::: (1989)
Fresno County Bar Association Conference delegates: Judy Soley, Fresno County Bar Association President G. Dana French, Patience Milrod and Judge Sandra Snyder